Katsuwonus pelamis Peptide and its Complexes Protect Zebrafish and Mice From Hyperuricemia Through Promoting Kidney Excretion of Uric Acid and Inhibiting Liver Xanthine Oxidase Activity - Wei, Wei; Zhou, Li-Jian; Wang, Shue; Zhang, Zheng; Huang, Jia-Ying; Zhang, Zhao; Zhang, Xi-Ping; Zhang, Xue-Jun; Li, Jie; Zhang, Ye-Wang (Frontiers in Chemistry, 2022)
Katsuwonus pelamis peptide and its complexes have the effect of lowering uric acid (UA)-levels. To identify the effect and the possible mechanisms, different concentrations of Katsuwonus pelamis peptide and its complexes were administered to the zebrafish and mice hyperuricemia models, and the UA level was measured. Meanwhile, the hyperuricemic mice were treated orally at 0.83, 1.67, and 5.00 mg/g body weight for 7 days with Katsuwonus pelamis peptide and the complexes groups, separately. The levels of serum UA (SUA), urinary UA (UUA), serum creatinine (SCR), blood urine nitrogen (BUN), and xanthine oxidase (XOD) activities were detected in each group. The results showed that Katsuwonus pelamis peptide (125 μg/mL) and its complexes (83.3 and 250 μg/mL) effectively reduced UA level in the zebrafish with hyperuricemia (P<0.05). Katsuwonus pelamis peptide at high concentration (5.00 mg/g) decreased the SUA level, SCR level, BUN level, and hepatic XOD activity, and the complexes (1.67 and 5.00 mg/g) significantly reduced SUA level and hepatic XOD activity (p<0.05) in the hyperuricemic mice. Additionally, in hyperuricemic mice model, the UUA level were increased after the treatment with Katsuwonus pelamis peptide and its complexes at high concentrations (p<0.05). The total therapeutic effects in Katsuwonus pelamis peptide complexes group were better than those in Katsuwonus pelamis peptide group. Thus, Katsuwonus pelamis peptide and its complexes hold a potential for hyperuricemia prevention and therapy, possibly through promoting urate secretion and inhibiting XOD activity production.